Optimization of DC Motor 80BL Using LQR Methods on MATLAB Simulink for Community Empowerment Applications - Anisa Fitri Santosa; Rama Arya Sobhita; Anggara Trisna Nugraha (Politeknik Perkapalan Negeri Surabaya, 2023)
Optimization techniques are essential tools for achieving the best possible outcomes in various fields, from engineering and economics to social sciences, including community empowerment. These techniques allow for optimal decision-making processes, especially in situations requiring minimal costs and maximum benefits. In the context of community service and empowerment, optimization techniques can enhance local initiatives, such as small-scale manufacturing, agricultural processes, and the development of community-based enterprises, by improving efficiency and reducing unnecessary costs. For example, in the design of infrastructure projects or the optimization of energy distribution systems, optimization techniques ensure that resources are used effectively to serve the community's needs. Moreover, by applying optimization methods, communities can enhance their self-sufficiency and contribute to sustainable development. The ability to minimize costs while maximizing utility can be a game-changer, particularly in underdeveloped areas where resources are limited. This research focuses on the optimization of a DC Motor 80BL using Linear Quadratic Regulator (LQR) methods on MATLAB Simulink, offering an advanced solution for community empowerment applications. LQR provides an optimal input that results in state feedback, represented by a constant gain within the system’s state, which can significantly improve the efficiency of various mechanical systems used in community-driven projects. The application of these optimization methods in community development ensures that local industries and projects can operate at their highest potential.